Effect of axial elongation on anterior scleral thickness in myopia - Hui Yan; Jie Li; Cheng Wang; Cai-Qiu Mei (Indian Journal of Ophthalmology)
Objective: This study aimed to investigate the effect of axial elongation on anterior scleral thickness (AST) in myopia. Methods: The convenience sampling method was used to select 122 patients without ocular or systemic diseases affecting ametropia in Ya’an People’s Hospital between March 2020 and January 2022. According to the diopter and axial length (AL), the patients were divided into an emmetropia group (32 cases), a low-to-moderate myopia group (40 cases), and a high myopia group (40 cases). Relevant data were collected and analyzed. Results: The AST of the four diameter lines was highest at the scleral process and measured. The results, in descending order, were as follows: temporal side (716.45 ± 65.55 μm), lower side (692.32 ± 74.76 μm), nasal side (671.54 ± 61.76 μm), and superior side (550.76 ± 51.34 μm). There was a correlation between the AL and the average AST of the four diameter lines. The correlations, from highest to lowest, were as follows: the mean AST of the nasal side (r = −0.455, P < 0.001), the mean AST of the upper side (r = −0.431, P < 0.001), the mean AST of the lower side (r = −0.402, P < 0.001) and the mean AST of the temporal side (r = −0.363, P < 0.001). Age was associated with the average AST of the upper, nasal, and temporal sides. The correlations, from highest to lowest, were as follows: the average AST of the upper side (r = 0.545, P < 0.001), the average AST of the temporal side (r = 0.422, P < 0.001), and the average AST of the nasal side (r = 0.411, P < 0.001). There were significant differences in AST among the three groups at 0, 1, 2, 3, 4, 5, and 6 mm from the scleral bulge (P < 0.05). AST was positively correlated with age and negatively correlated with AL (R2 = 0.432, F = 231.73, P < 0.05). Conclusion: The thickness of the sclera changed with the AL and measurement position. AST was negatively correlated with the AL and positively correlated with age. Compared with emmetropia and low-to-moderate myopia, the anterior sclera in cases of high myopia was thinner. Myopia affects not only the thickness of the posterior sclera but also the AST.